Improving ecological intelligence of students through the Utilization of inorganic waste in making flipchart as a Learning media of social science (classroom action research At smpn 3 lembang kab. Bandung barat class viii-b) - Aziizah, Nur Rohiimatullah (Universitas Pendidikan Indonesia, 2017)
Environmental disrespectful behavior such as the habit of littering, indifferent aboutthe consumption of the environmentally friendly products, then the lack of knowledge ofstudents about environment, also low ability of students in utilizing waste reflect that theecological intelligence of class VIII-B SMPN 3 lembang is still lacking. Therefore it isnecessary to take ways to improve the ecological intelligence of students. The effortsmade for that is by utilizing inorganic waste in making flipchart as a learning media ofsocial science. The expected objective of the research is improving the ecologicalintelligence of students in utilizing inorganic waste by describing started from planning,implementation, constraints and result of the improvement of the ecological intelligence ofstudents. The classroom action research uses model of Elliot. The result of the research,first, the planning process is conducted to determine SK/KD, preparing RPP includesapplying the flipchart media and preparing research instrument. Second, theimplementation process is implementing learning aligned with the planning of theresearch. Third, the constraints in the research is, the students are puzzled yet to determinethe theme of the flipchart which is made constraints, furthermore, make studentsconsciously keeping the environment around them. Fourth, the result in the research showsthe increasing in each cycle. Cycle I ecological intelligence of students in utilizinginorganic waste reached the category of â€œenoughâ€ that is 66.6%. Cycle II reached theâ€œgoodâ€ category that is 80.3%, and cycle III reached the â€œgoodâ€ category that is 82.8%.Therefore it can be concluded that the utilization of inorganic waste made as a media oflearning in the form of flipchart includes Including planning, implementation, andconstraints and results obtained could improve the ecological intelligence of students.